Evaluation of health promoting schools in Makkah city, Saudi Arabia - Elamin Bushara, Mohamed Osman; Ganbi, Mohamed; Elqarni, Mohamed; Terkstani, Abdulaziz; Lihyani, Rakan; AlHassani, Badr; Almuterfi, Hatem (International Journal Of Community Medicine And Public Health, 2017)
Background: The study was conducted to evaluate schools that implemented the health promotion program in Makkah city, which were 68 schools, (60%) of them randomly selected for the study. Methods: The seven components of the health promoting schools evaluated through descriptive cross sectional study, concentrating on the implementation activities of each component, and whether this implementation conforming to requested standards. Results: The study clarified that the health education activities scored 80% from the targeted activities in this component, encouragement of healthy behavior achieve the highest requested level, while healthy environment activities were being well implemented as it attained 87%. Conclusions: The study concluded that there were weaknesses in the following components, food and nutritional service, school health and mental service provision, and school connectedness with the surrounding community. The study recommends establishment of health service system for psychological and mental health for students, medical checks for school staff in addition to strengthening the links between health promoting schools and surrounding communities, through organized programs. The study recommends for more researches in order to support implementation of the program.